Development and Challenges of Standardized Testing in Kazakhstan: Transition from National to International Standards (Journal of Educational Sciences, 2023)
This article attempts to study the recent changes in standardized testing in Kazakhstan in recent years. This research aimed to analyze the national assessment policy, focusing on the building and challenges of the Unified National Test (UNT), the large-scale high-stakes examination from 2004 to the present. The study of the UNT data with geographical (urban and rural schools) and lingual (Kazakh and Russian schools) variables used statistical and comparative approaches in 2014, 2017, and 2020. An analysis of UNT results showed that changes to standardized testing in 2017 affected results in 2020, mainly in Kazakh-language schools in urban areas. The study’s results demonstrated that language significantly differed more significantly in rural than urban areas. In other words, rural areas affect Kazakh schools more than Russian ones in the considered years. These inconsistent findings can probably be explained by changes in the education policy regarding the UNT’s concept and its implementation started in 2017 when the UNT was transformed according to international standards of examination as the Program of International Student Assessment (PISA) and Scholastic Assessment Test (SAT).Keywords: school-based assessment, large-scale assessment, student evaluation, national assessment policy, quantitative analysis